A inclusão na educação básica: um olhar crítico sobre o uso da tecnologia assistiva nas práticas escolares inclusivas - Anthonisen, Gisele Rodegheiro de Moraes (2023)
This study is linked to the area of teacher training, assistive technology and inclusion, of the LP3 research line - Special education, inclusion and difference of the Postgraduate Program in Education at the Federal University of Santa Maria – UFSM. It is also linked to the research group Health Education and Inclusion Research Group - GEPEDUSI, and the Interdisciplinary Group in Education at this institution. To this end, the aim was to understand how the processes of inclusion of students with disabilities occur using assistive technology. We also sought to identify the use of assistive technology (AT) within the scope of pedagogical practice, investigating whether teacher training provided a basis for the use of AT. In this study, the research subjects were teachers who work in elementary school (1st to 9th grade) in the regular classroom, covering different subjects, in the municipality of Candiota/RS. The theoretical framework sought to characterize the processes of Inclusion, Assistive Technology and Teacher Training, through regulations, legislation and authors such as: Sassaki (2009), Pavão (2019), Kassar (2012), Sartoretto and Bresch (2002), Galvão Filho (2009), Manzini (2013), Michels (2018), Imbernón (2006), Zabala (1998), Tardif (2010), among others. According to the basic research methodology, with a qualitative, exploratory and descriptive approach, the procedure was a case study. To collect the data, an online form was used, with closed questions and some justified, grouped into categories to identify how the processes of inclusion, AT and teacher training are taking place in this context. Subsequently, the data collected was analyzed through dialogue with the theoretical framework. Finally, the concluding remarks point to the use of assistive technology as a preponderant factor in the inclusion process. However, in this process, it is necessary to provide teachers with training in the practical application of AT.